The Impact Of Electronic Accounting Information Systems On The Credibility Of Financial Statements From The Viewpoints Of External Auditors In Lybia - Adel Mohamed Hossin; Abdullah Mohammed Ayedh (Zes Rokman Resources, 2024)
Non-Indexed Publication